Mohawk - Russo, Richard, 1949- (Vintage contemporaries, 1994)
Mohawk, New York, is one of those small towns that lie almost entirely on the wrong side of the tracks. Its citizens, too, have fallen on hard times. Dallas Younger, a star athlete in high school, now drifts from tavern to poker game, losing money, and, inevitablym another set of false teeth. His ex-wife, Anne, is stuck in a losing battle with her mother over care of her sick father. And their son, Randall, is deliberately neglecting his school work because in a place like Mohawk is doesn't pay to be too smart.